The Analysis of Functional Morpheme in Hansel and Gretel Short Story - Paramita Kusumawardhani (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
The purpose of the research is to identify what functional morpheme is and how to recognize it in “Hansel and Gretel” short story. A functional morpheme is a part of free morpheme. A morpheme is the smallest unit in English linguistics that forms a word. There are two kinds of morpheme; they are free morpheme and bound morpheme. A morpheme that can stand on its own is called free, and ones that cannot are bound. A free morpheme has two types; they are lexical and functional morpheme. Functional morpheme is a morpheme that is commonly used in some articles to connect words or sentences. A functional morpheme is a part of Morphology. Functional morpheme is mostly used in English and it can be found in an English story. It is used because it gives influences the sentences. Without functional morpheme, sometimes the sentences will have no meaning or read awkwardly so it can give a different meaning to the sentences themselves. The data of the research was taken from “Hansel and Gretel” short story and the results of students’ analysis. The participants of the research were the 1st semester of English Department students. A qualitative descriptive method was used to do the research. After doing the research, there are some results found in the research, they are (1) two items in the article section; (2) four items for the conjunction part; (3) eight items for the preposition part; and (4) eight items in the pronoun section.